Kuwait : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper estimates the optimal allocation of government current spending, precautionary saving, and investment for Kuwait under uncertainty. The results show that in the face of high oil income volatility and the expected decline in oil prices, projected current spending exceeds the optimal amount over the medium term (2013-2018). However, there is room to increase investment spending, which should contribute to the growth of the tradable sector, as the projected investment rate is lower than the optimal investment rate of 20 percent of government income.